DESIGNING MAQASHID INDEX MEASUREMENT MODELS INTEGRATED WITH ESG IN ISLAMIC FINANCIAL INSTITUTIONS - Ahmad Fathul Maarif; Darmawan Darmawan; Siti Nor Amira Mohamad; Nurul Huda; Ahmad Fajar (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
This study aims to evaluate the performance of Islamic Financial Institutions (IFIs) through the integration of Maqashid Sharia principles and Environmental, Social, and Governance (ESG) criteria. The method used is Analytic Network Process (ANP), which allows the identification of priority aspects in performance measurement in a holistic manner.  The results show that the aspect of hifdzu ad-diin (protection of religion) is the highest priority in the maqashid objectives cluster. Meanwhile, in the ESG main criteria cluster, environmental aspects occupy the most dominant position. At the sub-criteria level, natural resource conservation (E), stakeholder awareness (S), and environmentally friendly policies (G) receive the highest weight. This study makes a new contribution by building an Islamic values-based performance measurement model integrated with ESG, which is relevant for realizing sustainable finance practices. This integration strengthens the evaluation approach to institutional sustainability, not only from an economic perspective, but also from social, ethical and environmental aspects.